Supply and demand of creatine and glycogen in broiler chicken embryos - Dayan, Jonathan; Melkman-Zehavi, Tal; Reicher, Naama; Braun, Ulrike; Inhuber, Vivienne; Mabjeesh, Sameer J.; Halevy, Orna; Uni, Zehava (Frontiers in Physiology, 2023)
Optimal embryonic development and growth of meat-type chickens (broilers) rely on incubation conditions (oxygen, heat, and humidity), on nutrients and on energy resources within the egg. Throughout incubation and according to the embryo’s energy balance, the main energy storage molecules (creatine and glycogen) are continuously utilized and synthesized, mainly in the embryonic liver, breast muscle, and the extraembryonic yolk sac (YS) tissue. During the last phase of incubation, as the embryo nears hatching, dynamic changes in energy metabolism occur. These changes may affect embryonic survival, hatchlings’ uniformity, quality and post hatch performance of broilers, hence, being of great importance to poultry production. Here, we followed the dynamics of creatine and glycogen from embryonic day (E)11 until hatch and up to chick placement at the farm. We showed that creatine is stored mainly in the breast muscle while glycogen is stored mainly in the YS tissue. Analysis of creatine synthesis genes revealed their expression in the liver, kidney, YS tissue and in the breast muscle, suggesting a full synthesis capacity in these tissues. Expression analysis of genes involved in gluconeogenesis, glycogenesis, and glycogenolysis, revealed that glycogen metabolism is most active in the liver. Nevertheless, due to the relatively large size of the breast muscle and YS tissue, their contribution to glycogen metabolism in embryos is valuable. Towards hatch, post E19, creatine levels in all tissues increased while glycogen levels dramatically decreased and reached low levels at hatch and at chick placement. This proves the utmost importance of creatine in energy supply to late-term embryos and hatchlings.